EFFECTIVENESS OF A GUIDEBOOK-BASED INTERVENTION IN IMPROVING PARENTAL KNOWLEDGE AND ACCESS TO SERVICES FOR CHILDREN WITH AUTISM SPECTRUM DISORDER IN HANOI (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness of a guidebook-based intervention on improving knowledge, attitudes, skills, and access to and utilization of services for children with autism spectrum disorder (ASD) among parents in Hanoi, Vietnam, 2024–2025.Methods: Pre–post intervention study without a control group was conducted among 191 parents or primary caregivers of children under 15 years of age diagnosed with ASD at five specialized centers in Hanoi. Participants received a structured guidebook on ASD care and service navigation and were assessed at baseline and after 3 and 6 months using standardized questionnaires on knowledge, attitudes, practices, and service use. Data were analyzed using descriptive statistics and paired pre–post comparison tests.Results: Following the intervention, the proportion of parents with adequate knowledge increased from 24.6% at baseline to 85.6% at 3 months and 96.5% at 6 months (p
Keywords: autism spectrum disorder; parent education; guidebook; community intervention; service access.